2014
DOI: 10.1016/j.jml.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Human locomotion in languages: Constraints on moving and meaning

Abstract: a b s t r a c tThe distinctions between red and yellow or arm and hand may seem self-evident to English speakers, but they are not: Languages differ in the named distinctions they make. To help understand what constrains word meaning and how variation arises, we examined name choices in English, Dutch, Spanish, and Japanese for 36 instances of human locomotion. Naming patterns showed commonalities largely interpretable in terms of perceived physical similarities among the instances. There was no evidence for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 44 publications
4
48
0
Order By: Relevance
“…A subsequent study was aimed at distinctions between a variety of manners of motion (Malt et al 2010(Malt et al , 2014. A student was videotaped while acting out a variety of expressive manners of motion, excluding those denoted by verbs "such as barge, bolt, bound, bump, and burst, which seem to capture elements of movement such as speed, suddenness, or gracefulness but not gait per se" (Malt et al 2010: 44).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study was aimed at distinctions between a variety of manners of motion (Malt et al 2010(Malt et al , 2014. A student was videotaped while acting out a variety of expressive manners of motion, excluding those denoted by verbs "such as barge, bolt, bound, bump, and burst, which seem to capture elements of movement such as speed, suddenness, or gracefulness but not gait per se" (Malt et al 2010: 44).…”
Section: Introductionmentioning
confidence: 99%
“…Majid et al argue that languages have a "general solution" to conceptualizing this domain and that, although there is variation, there are also strong constraints. Similar quantitative studies have considered motion verbs (Malt et al 2013) and adpositions for spatial relations (Levinson & Meira 2003), as well as morphological domains such as case (e.g., Clancy 2006). Malt et al (2014) suggest that the potential benefits (but also the constraints) of quantitative methods ought to inform approaches to collecting linguistic data so that methods become more standardized, systematic, and ecologically valid.…”
Section: Correlations In Semantic Domainsmentioning
confidence: 93%
“…In naming data, they found that speakers of English, Spanish, and Chinese differed more in the lexical distinctions they drew where clear clusters of exemplars in similarity space were absent (e.g., English bottle did not have a closely parallel lexical category in other languages). Similarly, Malt et al (2008Malt et al ( , 2014 examined the perceived similarity of instances of human locomotion and found two distinct clusters of instances contrasting in fundamental biomechanical properties (e.g., tiptoeing and walking vs. running and skipping; see below for discussion of this distinction). However, within each major group, they found a more continuous distribution of instances within each cluster.…”
Section: Word Learning and Structure In The Worldmentioning
confidence: 99%
“…The studies presented here examined naming by children aged four to nine for the same locomotion stimuli used by Malt et al (2008) and Malt et al (2014). The earlier studies compared adult naming across languages; here we focus on development for a single language.…”
Section: The Current Studiesmentioning
confidence: 99%
See 1 more Smart Citation